What drives Germany's exports? - Michael Frenkel; Lilli Zimmermann (International Journal of Management and Economics, 2020)
This article reviews several hypotheses that aim at explaining the development of German merchandise exports. Based on cointegration estimation techniques, we examine different determinants for their ability to explain German exports during the period 1992-2016. The estimation results indicate that, in addition to the traditional determinants (world demand and price competitiveness), other determinants, such as energy prices and the increasing fragmentation of production processes, are also crucial in explaining German exports.
Keywords: C22; F4; J3; 650; international trade; export demand; cointegration